PERAN SISTEM PENGENDALIAN MANAJEMEN DALAM PENERAPAN STRATEGI RELATIONSHIP MARKETING AZIZAH KONVEKSI DI DESA JATIRUNGGO KEC. PRINGAPUS - Viqi Miftakhul Faza; Afita Setyowati; Budi Utomo (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2021)
This research is a research about how the role of management control system in implementing relationship marketing strategy in a company. Where the name of the company certainly needs a strategy to increase sales. This study aims to determine the role of management control systems in implementing a relationship marketing strategy at a convection company located in the village of Jatirunggo, Kec. Pringapus. In this study, it was found that the production process had not run optimally due to rejected or defective products. Therefore, the convection party needs control in order to anticipate the damage that occurs to the products produced later. This control can be done by supervising activities at the time of production, selecting materials with good quality and providing training to the parties concerned with the production. Then, this convection Azizah distributed pamphlets through social media and posted pamphlets in crowded places to increase sales, orders and increase incoming orders. With so many customers from out of town working with Azizah convection